The Correlation Between Students' English Vocabulary and Their English Paragraph Writing Ability: Survey Study of 10th Grade Students at State 3 Senior High School Tangerang District - Hernindaria, Ratih Desi; Suryadi, Ace; Sudarmaji, Imam (Foremost Journal, 2022)
ABSTRACT The researcher is interested in finding out if students’ vocabulary mastery correlates with their writing skills. The 44 students were selected for this study using a purposive sampling technique, they were selected from the population of all the 10th grade students at State 3 Senior High School Tangerang District. A vocabulary test and a writing test were used to collect the data from the participants in this study. The Pearson Product Moment Correlation was used to examine the relationship between the two variables. The result shows that the coefficient between variable X and variable Y is 0.682. The criteria of correlation between two variables among 0.600 – 0.800 shows a high or strong correlation. The significant level at 5% is r-table = 0.297, it means rxy > r-table (0.682 > 0.297). The r-table significant level at 1 % is 0.384, it means that the rxy > r-table (0.682 > 0.384). The result of the analyses shows that there is a positive and significant correlation between students’ vocabulary mastery and students’ writing skill of State 3 Senior High School Tangerang District. Therefore, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. In other words, students who score high on vocabulary tests tend to have good writing skills too. Keywords: correlation, students’ vocabulary mastery, writing skills.